Intensity modulated radiation therapy with stereotactic body radiation therapy boost for unfavorable prostate cancer: five-year outcomes - Carrasquilla, Michael; Sholklapper, Tamir; Pepin, Abigail N.; Hodgins, Nicole; Lei, Siyuan; Rashid, Abdul; Danner, Malika; Zwart, Alan; Bolanos, Grecia; Ayoob, Marilyn; Yung, Thomas; Aghdam, Nima; et al. (Frontiers in Oncology, 2023)
Purpose Intensity-modulated radiation therapy (IMRT) with brachytherapy boost for unfavorable prostate cancer has been shown to improve biochemical relapse-free survival compared to IMRT alone. Stereotactic body radiation therapy (SBRT) is a less-invasive alternative to brachytherapy. Early outcomes utilizing SBRT boost suggest low rates of high-grade toxicity with a maintained patient-reported quality of life. Here, we report the 5-year progression-free survival (PFS) and prostate cancer-specific survival (PCSS) of patients treated with IMRT plus SBRT boost. Materials and methods Between 2008 and 2020, 255 patients with unfavorable prostate cancer were treated with robotic SBRT (19.5 Gy in three fractions) followed by fiducial-guided IMRT (45–50.4 Gy) according to an institutional protocol. For the first year, the patient’s PSA level was monitored every 3 months, biannually for 2 years, and annually thereafter. Failure was defined as nadir + 2 ng/mL or a rising PSA with imaging suggestive of recurrence. Detection of recurrence also included digital rectal examination and imaging studies, such as MRI, CT, PET/CT, and/or bone scans. PFS and PCSS were calculated using the Kaplan–Meier method. Results The median follow-up period was 71 months. According to the NCCN risk classification, 5% (13/255) of the patients had favorable intermediate-risk disease, 23% (57/255) had unfavorable intermediate-risk disease, 40% (102/255) had high-risk disease, and 32% (83/255) had very high-risk disease. Androgen deprivation therapy was administered to 80% (204/255) of the patients. Elective pelvic lymph node IMRT was performed in 28 (10%) patients. The PFS for all patients at 5 years was 81% (favorable intermediate risk, 91%; unfavorable intermediate risk, 89%; high-risk, 78%; and very-high risk, 72%). The PCSS for all patients at 5 years was 97% (favorable intermediate risk, 100%; unfavorable intermediate risk, 100%; high risk, 100%; and very high risk, 89%). Conclusion The incidence of failure following IMRT plus SBRT for unfavorable prostate cancer remains low at 5 years.